Clusters of megaearthquakes on upper plate faults control the Eastern Mediterranean hazard. Issue 23 (14th December 2015) - Mouslopoulou, Vasiliki; Nicol, Andrew; Begg, John; Oncken, Onno; Moreno, Marcos
Abstract: The Hellenic subduction margin in the Eastern Mediterranean has generated devastating historical earthquakes and tsunamis with poorly known recurrence intervals. Here stranded paleoshorelines indicate strong uplift transients (0–7 mm/yr) along the island of Crete during the last 50 kyr due to earthquake clustering. We identify the highest uplift rates in western Crete since the demise of the Minoan civilization and along the entire island between 10 and 20 kyr B.P., with the absence of uplifted Late Holocene paleoshorelines in the east being due to seismic quiescence. Numerical models show that uplift along the Hellenic margin is primarily achieved by great earthquakes on major reverse faults in the upper plate with little contribution from plate‐interface slip. These earthquakes were strongly clustered with recurrence intervals ranging from hundreds to thousands of years and primarily being achieved by fault interactions. Future great earthquakes will rupture seismically quiet areas in eastern Crete, elevating both seismic and tsunami hazards. Key Points: Uplift along the Hellenic forearc transient due to earthquake clustering Earthquakes occur mostly on upper plate faults rather than the plate interface Seismic hazard in Eastern Mediterranean underestimated